The 30-15 Intermittent Fitness Test: A Reliable, Valid, and Useful Tool to Assess Aerobic Capacity in Female Basketball Players. Issue 1 (2nd January 2020) - Jeličić, Mario; Ivančev, Vladimir; Čular, Dražen; Čović, Nedim; Stojanović, Emilija; Scanlan, Aaron T.; Milanović, Zoran
ABSTRACT: Purpose : The purpose of this study was to determine the reliability, validity, and usefulness of 30–15 Intermittent Fitness Test (30-15IFT ) in female basketball players. Methods : Nineteen female basketball players (17.82 ± 1.94 yr, 175.4 ± 7.3 cm, 67.9 ± 7.7 kg) competing in the National Croatian League performed one trial of a continuous treadmill running test and two trials of the 30-15IFT . The 30-15IFT involves 30-s runs across a 40-m course interspersed with 15 s of walking, with running speed increasing every 45 s. The continuous treadmill running test was used as the criterion for validation. Results : High to very high reliability across test–retest trials were observed for maximal oxygen uptake (VO2 max) (CV = 4.9%, ICC = 0.85), the 30-15IFT end-running velocity (VIFT ) (CV = 6.0%, ICC = 0.85), and maximal heart rate (HRmax) (CV = 4.8%, ICC = 0.96). Criterion validity was supported for the 30-15IFT with strong to very strong relationships with VO2 max ( r = 0.69), VIFT ( r = 0.74), and HRmax ( r = 0.73) attained during the continuous treadmill running test. The typical error (TE) of the 30-15IFT was greater than the smallest worthwhile change for VO2 max (1.16 > 0.42 ml/kg/min), VIFT (0.56 > 0.20 km/h), and HRmax (2.15 > 1.89 bpm) adjudging usefulness of the test as marginal . The TE of 0.56 km/h (90% CI = 0.44–0.77 km/h) demonstrates changes in the performance of one to two stages (0.5–1.0 km/h) are meaningful. Conclusions : The 30-15IFT possesses acceptable reliability and validity to assess maximal aerobic fitness capacity in female basketball players. While the usefulness of the 30-15IFT was marginal, meaningful changes in performance consisted of only one to two stages. The present findings support the 30-15IFT as a practical testing option for basketball practitioners to assess fitness capacities in female players.